Potent and Selective BACE-1 Peptide Inhibitors Lower Brain Aβ Levels Mediated by Brain Shuttle Transport - Ruderisch, Nadine (EBioMedicine, 2017)
Therapeutic approaches to fight Alzheimer's disease include anti-Amyloidβ (Aβ) antibodies and secretase inhibitors. However, the blood-brain barrier (BBB) limits the brain exposure of biologics and the chemical space for small molecules to be BBB permeable. The Brain Shuttle (BS) technology is capable of shuttling large molecules into the brain. This allows for new types of therapeutic modalities engineered for optimal efficacy on the molecular target in the brain independent of brain penetrating properties. To this end, we designed BACE1 peptide inhibitors with varying lipid modifications with single-digit picomolar cellular potency. Secondly, we generated active-exosite peptides with structurally confirmed dual binding mode and improved potency. When fused to the BS via sortase coupling, these BACE1 inhibitors significantly reduced brain Aβ levels in mice after intravenous administration. In plasma, both BS and non-BS BACE1 inhibitor peptides induced a significant time- and dose-dependent decrease of Aβ. Our results demonstrate that the BS is essential for BACE1 peptide inhibitors to be efficacious in the brain and active-exosite design of BACE1 peptide inhibitors together with lipid modification may be of therapeutic relevance.